SOUND WAVE IN PLANT GROWTH REGULATION: A REVIEW OF POTENTIAL BIOTECHNOLOGICAL APPLICATIONS - Tapan Kumar Mohanta (Journal of Animal and Plant Sciences, 2018)
The sound wave perception of the animal is one of the most important mediums of communication. It contributed significantly in shaping the behavior, ecology and evolution of the organism. This evolutionary conserved communication mechanism in animal is carried out by different specialized organs like ear, antenna and others. However, the sessile organism, plants lack the specialized organ for the perception of sound and still perceive the sound signal. The sound wave perception in plants might also play critical role in shaping ecological and evolutionary implication. The effect of sound waves in the plant might have an advantageous effect which allows it to learn about the surrounding environment using the acoustic energy. The perceptions of sound signal in plants can lead to increase in growth, development and yield potential of plants. Therefore, sound wave treatment in the plant can be used as one of the growth promoter/regulator to increase the yield potential of crops. However, it is yet to identify the molecular receptor that perceives the sound wave in plants. The mechano-sensitive ion channels present in plasma membrane are highly modulated due to sound wave treatment that leads to differential calcium signaling in plants and subsequent regulation of downstream signaling molecules. In this review, author has reported some basic concept of the sound wave research and modulation of molecular responses in plant at cellular and sub-cellular level upon treatment of sound waves.
Keywords: Sound wave; Hertz; Decibel; Acoustic energy